An inflammatory link in atherosclerosis and obesity - Zirlik, A.; Lutgens, E. (Hämostaseologie, 2015)
Atherosclerosis and obesity-induced metabolic dysfunction are lipid-driven inflammatory pathologies responsible for a major part of cardiovascular complications. Immune cell activation as well as interactions between the different immune cells is dependent on and controlled by a variety of co-stimulatory signals. These co-stimulatory signals can either aggravate or ameliorate the disease depending on the stage of the disease, the cell-types involved and the signal transduction cascades initiated. This review focuses on the diverse roles of the most established co-stimulatory molecules of the B7 and Tumor Necrosis Factor Receptor (TNFR) families, ie the CD28/CTLA4-CD80/CD86 and CD40L/CD40 dyads in the pathogenesis of atherosclerosis and obesity. In addition, we will explore their potential as therapeutic targets in both atherosclerosis and obesity.
Keywords: Atherosclerosis; obesity; co-stimulation